2016
DOI: 10.1515/amtm-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Laser borided composite layer produced on austenitic 316L steel

Abstract: A B S T R A C TAustenitic 316L steel is well-known for its good resistance to corrosion and oxidation. Therefore, this material is often used wherever corrosive media or high temperatures are to be expected. The main drawback of this material is very low hardness and low resistance to mechanical wear. In this study, the laser boriding was used in order to improve the wear behavior of this material. As a consequence, a composite surface layer was produced. The microstructure of laser-borided steel was character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The examination of the borided coating layer morphologies showed the existence of a compact layer structure and a clearly visible interface between the matrix and the borided layer is clearly visible and the layer has a compact structure. While a saw-toothed morphology was reported for the boride layer in the previous studies due to the low concentration of carbon [12,22,23], a planar morphology was observed in this study due to high alloy ratios of the materials, as shown in the literature [24,25]. As the carbon content of the matrix material and the ratio of the alloying elements increase, a more planar morphology was encountered, as the toothed structure expected to form on the matrix interface of the boride layer was suppressed [26].…”
Section: Resultssupporting
confidence: 51%
“…The examination of the borided coating layer morphologies showed the existence of a compact layer structure and a clearly visible interface between the matrix and the borided layer is clearly visible and the layer has a compact structure. While a saw-toothed morphology was reported for the boride layer in the previous studies due to the low concentration of carbon [12,22,23], a planar morphology was observed in this study due to high alloy ratios of the materials, as shown in the literature [24,25]. As the carbon content of the matrix material and the ratio of the alloying elements increase, a more planar morphology was encountered, as the toothed structure expected to form on the matrix interface of the boride layer was suppressed [26].…”
Section: Resultssupporting
confidence: 51%
“…Boroaluminizing at 1050°C leads to the formation of layers with a composite structure, where solid structural components, for instance iron borides, are arranged in the form of isolated inclusions, and more viscous components form a matrix (Fig. 6) [7][8][9]. This type of structure provides high mechanical properties, in particular -wear resistance and plasticity (low brittleness).…”
Section: Resultsmentioning
confidence: 99%
“…Exothermic heating is provided by simpler equipment, but its flow is difficult to regulate and control. Laser heating requires certain equipment [7,8]. Induction heating also requires equipment, but an order of magnitude simpler and cheaper.…”
Section: Introductionmentioning
confidence: 99%